Bacterial Assessment of Ready to Eat Sweet (Burfi) Sold in Different Sweet Houses in Narayangadh, Chitwan: A Pilot Study - Basnet, H. B.; Deubanjar, M. (Nepalese Veterinary Journal, 2019)
As a sweet product, burfi is highly esteemed by Nepalese consumer and kept in high priority from the time immemorial. However, the milk and milk products borne outbreaks account for 2 to 6 % of bacterial foodborne outbreaks in several countries. Hence, with an objective to determine the bacterial load of the commercial sweet (burfi) sold in Bharatpur metropolitan city 1, Narayangadh, Chitwan, a cross-sectional study was conducted. Ten sample of ready to eat sweet (Burfi) along with the packaging material were collected purposively from different sweet shops of Bharatpur metropolitan on January 2019. The preparation of samples was done as per Food Microbiology Protocols (2001) and the aerobic colony count (ACC) was determined by spread plate technique using plate count agar. It was found that the aerobic plate count of burfi sample ranges from 9.1×109 to 1.5×1010 CFU/g with an average of 1.2×1010 CFU/g, which is higher than the permissible Standard Plate Count according to Indian Standards Institution (ISI) specification. In conclusion, the high bacterial count in Burfi samples from different sweet shops indicates insufficient hygienic condition duration handling and unhygienic conditions of storage. This may give rise to public health hazard.